Organizational justice, psychological distress, and stress-related behaviors by occupational class in female Japanese employees. - Yumiko Kobayashi; Naoki Kondo (PLoS ONE, 2019)
Backgrounds Recent evidence has suggested that in Japan, professionals and managers have a higher risk of poor health than other workers (e.g., clerks and manual laborers), and this effect may be stronger among women than men. Low organizational justice, which is known to be a potential risk factor for poor health among employees, may explain the gender-specific association. Methods We examined the associations between perceived organizational justice and psychological distress and stress-related behaviors (smoking and heavy drinking) in 2,216 female and 7,557 male employees aged 18 to 69 years from the Japanese Study of Health, Occupation, and Psychosocial Factors Related Equity. We measured both procedural and interactional justice, and compared managers and professionals with other employees. Results After adjusting for demographic characteristics and occupational stress, low levels of perceived procedural and interactional justice were found to be associated with a high prevalence of psychological distress for both women and men, regardless of occupational status. Among female managers and professionals, perceived interactional justice (measured as the levels of supports by supervisors, etc.) was significantly associated with smoking, whereas no such association was observed among other workers. When interactional justice was perceived to be low, the prevalence of smoking was 6.5 percentage points higher among managers and professionals than among others. Neither procedural nor interactional justice was associated with risk of heavy drinking. Conclusions Female managers and professionals in a workplace with unsupportive supervisors may be more likely to engage in unhealthy coping behaviors to manage their stress. Creating supportive workplaces may be beneficial in increasing workers' health, especially for female managers and professionals.